Evidence moderately supports effectiveness of interventions targeting mealtime difficulties in older adults with dementia. Issue 2 (2nd April 2016) - O'Neil-Pirozzi, Therese M.; Perrone, Courtney
Abstract : This review provides a summary and appraisal commentary on the treatment review by Liu, W., Cheon, J., & Thomas, S. A. (2014). Interventions on mealtime difficulties in older adults with dementia: A systemaic review. International Journal of Nursing Studies, 51, 14–27. Source of funding and declaration of interest: Declared no funding and no conflicts of interest.